Analysis of Frequently Appearing Words in the Titles of 2023 Research Grant Winners in Indonesia Using the TF-IDF Method - Setiawan, Rudi; Kisman, Zainul; Imam, Asep (Journal of Information System and Informatics, 2023)
Research activities are an obligation to be carried out by a lecturer, each year the Government of Indonesia through the Ministry of Education, Culture, Research and Technology encourages the improvement of research through a large amount of research funding aid through several schemes of grant competition. By 2023, the percentage of proposals funded was only 22.7% of the total of research proposals submitted as 28.404. One of the problems that arises for the lecturer who follows the research grant is to determine the title of the research. The research aims to identify the words that often appear on the research titles that escape funding from each grant scheme by performing word grinding using the TF-IDF method. The results of this research indicate that in the novice lecturer research grant scheme (PDP) the word that often appears is the word "based" with a total of 434 proposals, in the regular fundamental research (PFR) the word that often appears is "development" of 374 proposals , domestic cooperation research (PKDN) the word that often appears is "based" with 117 proposals, post-graduate research doctoral dissertation research (PPS-PDD) the word that often appears is "model" with 154 proposals, in post-graduate research master's thesis research (PTS-PTM) words that often appear "based" are 191 proposals and in the downstream applied research scheme (PT-JH) words that often appear "based" are 82 proposals. This research can provide an overview of the names of titles funded based on the highest number of occurrences of a word from all titles funded. The words "based", "development" and "model" are the 3 largest words that appear in the titles of proposals funded in the PFR, PKDN, PPS-PDD, PPS-PTM, and PT-JH schemes. For the PDP scheme, the order of the 3 largest words that appear in the title of the proposal is "based", "regency", and "development".